Confronting moral distress in Nursing: recognizing nurses as moral agents - Franco A. Carnevale (Associação Brasileira de Enfermagem, 2013)
The concept of moral distress has brought forth a substantively different way of understanding some of the difficulties confronted by nurses in their practice. This concept highlights that nurses' distress can be an indication of nurses' conscientious moral engagement with their professional practice that has confronted practices or an environment that impedes them from acting according to their own ethical standards. Moral distress can be an indicator of problems in nurses' practice environments. This concept is described and related to moral agency in nursing practice. Selected research on moral distress is reviewed, followed by a discussion of recommendations for addressing this problem.